Let's talk about race ebook - Lester, Julius (2020)
"This wonderful book should be a first choice for all collections and is strongly recommended as a springboard for discussions about differences." —School Library Journal (starred review) In this acclaimed book, the author of the Newbery Honor Book To Be a Slave shares his own story as he explores what makes each of us special. A strong choice for sharing at home or in the classroom. Karen Barbour's dramatic, vibrant paintings speak to the heart of Lester's unique vision, truly a celebration of all of us. "This stunning picture book introduces race as just one of many chapters in a person's story" (School Library Journal). "Lester's poignant picture book helps children learn, grow, discuss, and begin to create a future that resolves differences" (Children's Literature). Julius Lester said: "I write because our lives are stories. If enough of these stories are told, then perhaps we will begin to see that our lives are the same story. The differences are merely in the details." I am a story. So are you. So is everyone.